English Teachers’ Strategy in Teaching Writing Descriptive Text to Students of All-Grades at Junior High School - Reza Luthfi; Berlin Sibarani (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2021)
This research was aimed at describing the extent to which strategy does the teachers use in teaching descriptive writing to students at Junior High School and finds out the reasons underlying the teachers using certain theory. The strategy which the teachers use was analyzed by following the theory of Johns’ Scaffolding Strategy (2010). Scaffolding Strategy divided into Explicit Implementation consist of three types namely (1) modeling; (2) joint negotiation and (3) independent construction. And the other one is Implicit Implementation which consists of four types namely (1) dimly felt of sense; (2) begin composing; (3) course composing and (4) external feedback. The data was analyzed following Miles and Huberman theory of qualitative research (1994). The research findings showed that, the English teachers are using all three types of explicit implementation and only one type of implicit implementations, namely external feedback. And the reasons underlying teachers using these implementations are (1) the teachers want to vivid students’ knowledge about the generic structure, language features and social functions of descriptive text, (2) teachers want the students to understand more and get familiar with descriptive text in real life, (3) teachers wants to know students’ ability in applying their knowledge of descriptive text on their own-making descriptive text and (4) enlighten students on how to criticize their friends’ work.Keywords: Descriptive, scaffolding, explicit implementation, implicit implementation